INTERFERENSI DIALEK MADURA DALAM PELAFALAN HURUF HIJAIYAH SISWA MADRASAH IBTIDAIYAH - Latifatul Mahbubah (Al-Mudarris: Journal Of Education, 2024)
Language interference is still an interesting topic to research, especially for language observers, This is influenced by the variety of regional languages ​​or mother tongues used in Indonesia. This research aims to determine the interference of the Madurese dialect in the pronunciation of the Hijaiyah letters of Madrasah Ibtidaiyah students during the implementation of Arabic language learning at school. This research uses descriptive qualitative research methods using several data analysis processes, namely data collection, data reduction, data verification, data presentation and conclusions. The results of the research show that Madurese dialect interference in the pronunciation of the hijaiyah letters of class VI MI Nurus Salam Pamekasan students has two forms, namely changing the sound of certain letters into the sound of other letters which are almost similar in articulation and the presence of inaccurate articulation of certain letters such as the letters ب، ج، د and several other letters